Influence of the growing conditions on thermochromic properties of [NH₂(C₂H₅)₂]₂CuₓZn₁-ₓCl₄ crystals - Kapustianyk, V.; Korchak, Yu.; Rudyk, V.; Batiuk, A. (Functional Materials, 2005)
The absorption spectra of [NН₂(C₂Н₅)₂]₂CuCI₄ crystals grown from ethanol solution as well as of [NН₂(C₂Н₅)₂]₂ZnCI₄ ‧nН₂О, [NН₂(C₂Н₅)₂]₂Cu₀.₂₅Zn₀.₇₅CI₄ crystals grown from water solutions have been investigated in the visible spectral region. The influence of ionizing irradiation on these spectra has been studied as well. The [NН₂(C₂Н₅)₂]₂CuCI₄ crystal grown from the ethanol solution has been shown to undergo the thermochromic phase transition at a higher temperature (Тᴛ ʰ = 324.5 К) and to manifest a higher sensitivity to ionizing irradiation influence as compared to the similar crystal grown from water solution. 75 % substitution of copper ions by zinc at the Transition to [NН₂(C₂Н₅)₂]₂Cu₀.₂₅Zn₀.₇₅CI₄ solid solution results in the change of the thermochromic phase transition character from the discontinuous to continuous one. The high sensitivity of the exciton absorption band long-wave edge location to low doses of ionizing radiation in [NН₂(C₂Н₅)₂]₂ZnCI₄‧nН₂О hydrated crystal has been revealed. Исследованы спектры поглощения кристаллов [NН₂(C₂Н₅)₂]₂CuCI₄, выращенных из спиртового раствора, и [NН₂(C₂Н₅)₂]₂ZnCI₄‧nН₂О, [NН₂(C₂Н₅)₂]₂Cu₀.₂₅Zn₀.₇₅CI₄ выращенных из водных растворов, в видимой области спектра, а также влияние на них ионизирующего облучения. Показано, что кристалл [NН₂(C₂Н₅)₂]₂CuCI₄, выращенный из спиртового раствора, претерпевает термохромный фазовый переход при более высокой температуре (Тᴛ ʰ = 324.5 К) в сравнении с аналогичным кристаллом, выращенным из водного раствора, а также имеет более высокую чувствительность к ионизирующему облучению. 75 %-ное замещение ионов меди ионами цинка при переходе к твердому раствору [NН₂(C₂Н₅)₂]₂Cu₀.₂₅Zn₀.₇₅CI₄ сопровождается изменением характера термохромного фазового перехода со скачкообразного на непрерывный. Обнаружено высокую чувствительность положения длинноволнового края экситонной полосы поглощения в кристаллогидрате [NН₂(C₂Н₅)₂]₂ZnCI₄‧nН₂О к малым дозам ионизирующего излучения. Дослiджено спектри поглинання кристалiв [NН₂(C₂Н₅)₂]₂CuCI₄, вирощених зi спиртового розчину, i [NН₂(C₂Н₅)₂]₂ZnCI₄ ‧nН₂О, [NН₂(C₂Н₅)₂]₂Cu₀.₂₅Zn₀.₇₅CI₄, вирощених iз водних розчинiв, у видимiй областi спектра та вплив на них iонiзуючого опромiнення. Показано, що кристал [NН₂(C₂Н₅)₂]₂CuCI₄, вирощений зi спиртового розчину, зазнає термохромний фазовий перехiд при вищiй температурi (Тᴛ ʰ = 324.5 К) у порiвняннi з аналогiчним кристалом, вирощеним з водного розчину, а також має вищу чутливiсть до дiї iонiзуючого опромiнення. 75 %-не замiщення iонiв мiдi iонами цинку при переходi до твердого розчину [NН₂(C₂Н₅)₂]₂Cu₀.₂₅Zn₀.₇₅CI₄ супроводжується змiною характеру термохромного фазового переходу зi стрибкоподiбного на неперервний. Виявлено високу чутливiсть положення довгохвильового краю екситонної смуги поглинання у кристалогiдратi [NН₂(C₂Н₅)₂]₂ZnCI₄‧nН₂О до малих доз iонiзуючого випромiнювання.